Coupling and Reforming of Methane with Carbon Dioxide in a Pulsed Plasma - OUYANG, FENG; YAO, SHUILIANG; SUZUKI, EIJI; NAKAYAMA, AKIRA; MIZUNO, AKIRA; OKUMOTO, MAMORU (KAGAKU KOGAKU RONBUNSHU, 2000)
Coupling and reforming of methane with carbon dioxide were studied at room temperature and 773 K in a pulsed plasma. Methane and carbon dioxide could be converted mainly to ethylene, carbon monoxide, and hydrogen at room temperature. At 773K, the main product was ethane at a low pulse frequency and ethylene at a high pulse frequency. The energy efficiency can be significantly improved by using a high pulse frequency and high temperature.